Recent advances of nanocellulose as biobased adsorbent for heavy metal ions removal: A sustainable approach integrating with waste management - Pandey A.; Kalamdhad A.; Chandra Sharma Y. (My University, 2025)
Fast-track industrialization and unplanned urbanization have triggered environmental pollution considerably. These anthropogenic activities have led to the discharge of huge quantities of waste into water. As a result, the surface and groundwaters are heavily contaminated with organic and inorganic pollutants including heavy metals. Heavy metals are highly carcinogenic and lethal. Decontamination of heavy metals from drinking water has always been a challenge. Conventional water treatment methods are cost-ineffective, energy-intensive, and produce huge toxic wastes. In this endeavour, researchers have developed bio-based adsorption technique for heavy metal ions' removal from polluted water. Nanocelluloses (NCs) as biosorbents have garnered significant interest due to their specialties like; presence of plentiful –OH groups on its surface rendering the incorporation of chemical moieties, high specific surface area, mechanical strength, recyclability, and biodegradability. This review provides a comprehensive detail about methods of nanocellulose production and its salient properties. Application of NC based adsorbents for water treatment methods depends on many factors like its synthesis routes, surface functionalization, specific surface area, regenerative capacity and reusability, etc. Recent advancements on production of biosorbents instigate on implementation of bioderived NC based adsorbents for water treatment technologies. This paper also demonstrates that exploiting the potentials of agricultural wastes, particularly sugarcane bagasse (SCB) as precursor for nanocelluloses puts forward a sustainable approach viz. the conversion of negatively valued waste into definite high value product and its utilization in wastewater treatment. © 2023 Elsevier B.V.